Exploring educational inequalities in hypertension control, salt knowledge and awareness, and patient advice: insights from the WHO STEPS surveys of adults from nine Eastern European and Central Asian countries - Katerina Maximova; Enrique Loyola Elizondo; Holly Rippin; João Breda; Francesco P Cappuccio; Morteza Hajihosseini; Kremlin Wickramasinghe; Irina Novik; Vital Pisaryk; Lela Sturua; Ainura Akmatova; Galina Obreja; et al. (Cambridge University Press, 2023)
Abstract Objective: To inform strategies aimed at improving blood pressure (BP) control and reducing salt intake, we assessed educational inequalities in high blood pressure (HBP) awareness, treatment and control; physician's advice on salt reduction; and salt knowledge, perceptions and consumption behaviours in Eastern Europe and Central Asia. Design: Data were collected in cross-sectional, population-based nationally representative surveys, using a multi-stage clustered sampling design. Five HBP awareness, treatment and control categories were created from measured BP and hypertension medication use. Education and other variables were self-reported. Weighted multinomial mixed-effects regression models, adjusted for confounders, were used to assess differences across education categories. Settings: Nine Eastern European and Central Asian countries (Armenia, Azerbaijan, Belarus, Georgia, Kyrgyzstan, Republic of Moldova, Tajikistan, Turkey and Uzbekistan). Participants: Nationally representative samples of 30 455 adults aged 25-65 years. Results: HBP awareness, treatment and control varied substantially by education. The coverage of physician's advice on salt was less frequent among participants with lower education, and those with untreated HBP or unaware of their HBP. The education gradient was evident in salt knowledge and perceptions of salt intake but not in salt consumption behaviours. Improved salt knowledge and perceptions were more prevalent among participants who received physician's advice on salt reduction. Conclusions: There is a strong education gradient in HBP awareness, treatment and control as well as salt knowledge and perceived intake. Enhancements in public and patient knowledge and awareness of HBP and its risk factors targeting socio-economically disadvantaged groups are urgently needed to alleviate the growing HBP burden in low- and middle-income countries.